Arming Anti-EGFRvIII CAR-T With TGFβ Trap Improves Antitumor Efficacy in Glioma Mouse Models - Li, You; Wu, Huifang; Chen, Gang; Wei, Xiaofan; Wang, Chunyu; Zhou, Shanshan; Huang, Ailing; Zhang, Zui; Zhan, Changyou; Wu, Yanling; Ying, Tianlei (Frontiers in Oncology, 2020)
Glioblastoma (GBM) is an aggressive malignancy with poor prognosis. New therapeutic strategies for GBM are urgently needed. Although clinical studies have demonstrated the feasibility and safety of chimeric antigen receptor (CAR) T cell therapy for GBM, its efficacy has not been that impressive. The major limitation for anti-tumor efficacy of CAR-Ts is the immunosuppressive milieu of the GBM tumor microenvironment (TME). TGFβ, a substantial component in GBM, compromises the immune response and contributes to immune evasion and tumor progression. To overcome this limitation and improve the efficacy of CAR-T cells for GBM, we optimized an EGFRvIII-specific CAR construct with TGFRII ectodomain as a TGFβ-trap and generated TGFβ-resistant CAR-Ts for GBM therapy. We demonstrated that this TGFβ-trapped architecture enhanced anti-tumor efficacy of EGFRvIII-specific CAR-T and prolonged the survival of mice bearing GBM. In addition, the GBM-infiltrated microglia, typically considered tumorigenic, showed increased expression of M1 polarization markers after treatment with the TGFβ-trap CAR-Ts group, indicating that these microglia were polarized toward a pro-inflammatory and anti-tumorigenic phenotype. Overall, these results indicated that arming CAR-T cells with a TGFβ-trap diminishes the immunosuppressive effect and is a potential strategy to improve CAR-T efficacy for GBM therapy.